Improving Mental Health Outcome in Hypertensive Patients: The Role of Relaxation Techniques - Alaa Abed Atiyah; Dergham Majeed Hameed (Kufa Journal for Nursing Sciences)
Background: Relaxation techniques (progressive muscle relaxation and deep breathing) have an impact on the patients with hypertension as they produce a relaxation response within the body and thus, are efficient in lowering the stress and blood pressure in the patients.